(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Alcohol abuse is also a major health issue affecting the United Kingdom as it gives a disease burden, hospitalization, and mortality particularly in people aged 15 to 49 years. The alcohol-related damage is preventable, and such interventions as Brief Interventions (BIS) within the primary and community health care have shown that such an intake and associated dangers could be diminished. Aims and objective: It is a systematic review that takes into account the effectiveness of the shorter interventions in the reduction of alcohol misuse in community-based healthcare services such as general practice services (GPs) and pharmacies in the UK. Methods: The databases were systematically searched like EBSCO Medline, EMBASE Ovid, PLOS Medicine, BMJ, PubMed, Cochrane Library, Scopus and PsycINFO. Published articles that were included in 2000-2022 were those that were full-text randomized controlled trials (RCTs), or quasi-experiments that evaluated the use of BIs in alcohol reduction. The extraction, synthesis, and critique of the data were carried out using the Critical Appraisal Skills Program (CASP) checklist. Results: Through the number of studies (342) that were identified, nine studies were incorporated (eight RCT and one quasi-experiment). The research showed that BIs provided within community-based and hospital settings can be useful in eliminating the usage of alcohol and related damages. Such interventions by general practitioners and practice nurses were found to be moderate success in particular combination with motivational interviewing or structured counselling. However different results were obtained depending on the mode of delivery, provider, and patient interaction. The interventions based on electronic or application turned out to possess the potential of scalable assistance and lacked consistency of effects in the long term. Few published findings have been done in investigating the role of pharmacists. Conclusion: Brief intervention is an effective tool of preventing alcohol misuse particularly in primary care wherein qualified health care givers will carry out the interventions. The long-term outcomes will be achieved through the constant interaction with the patients and consciousness by the provider. The researchers should consider introducing digital technologies and interventions facilitated by pharmacists in the future to make them more accessible and effective.